PJBL: MENINGKATKAN KEAKTIFAN PESERTA DIDIK DI SMA - Indrayani, Pungki; Apriani Fr, Dewi; Hendaryati, Neni; Nafiati, Dewi Amaliah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Abstract Education is an effort to increase the nation's intelligence and improve the quality of society in Indonesia. It is important that teachers and students work together to achieve educational goals. However, often the learning process is still focused on the role of the teacher, the use of less innovative lecture methods causes students to become bored and less active. The method applied in this research is literature study. There is various evidence that supports the PjBL learning model to increase student activity. It should be remembered that supervision and guidance from educators is still needed to ensure the successful implementation of this learning model. Based on the results of the literature study, it can be concluded that the PjBL learning model is effective in increasing student activity in high school level economics subjects. The use of the PjBL model in learning activities results in increased student learning activities. The stages in the PjBL model show significant potential in increasing student activity. However, to successfully implement this learning model, educator creativity is also very important.